The global governance of marine plastic pollution: rethinking the extended producer responsibility system - Zhou, Jiang; Luo, Di (Frontiers in Marine Science, 2024)
The harm caused by marine plastic pollution to the wider environment highlights its importance as a governance issue. The Fifth United Nations Environment Assembly (UNEA) adopted a resolution, “End Plastic Pollution: Towards an International Legally Binding Instrument”, which represents a shift towards globalism in the governance of marine plastic pollution. This resolution focuses on the circular economy of plastics and highlights the role of corporations in contributing to a more socially responsible society, thereby increasing emphasis has been placed on the Extended Producer Responsibility (EPR) system that integrates the two factors referred to above. This paper provides a full technical explanation of the EPR system and its implementation in entities such as the European Union, the United States, and China. The challenges faced when integrating the EPR system into international legal instruments for plastic governance were identified, including the different national perspectives, the absence of a supervisor in the public domain, the obscurity of its application, and the lack of supporting measures for the implementation of the system. Therefore, new standards and requirements in the governance of marine plastic pollution and the advantages associated with implementing the full-life-cycle obligations under the EPR system on plastic producers should be fully considered. On this basis, the positioning and implications of the EPR system should be clarified by obligation-oriented regulation and extension-based interpretation. Moreover, the extended and prolonged applicability of the system, including the original sources of marine plastic wastes and considerations of the full-life-cycle of plastics, should be achieved in pursuit of improvements and upgrades in application and complementary policies. If this can be achieved, it is hoped that the goals of protecting human health and controlling plastic pollution can be achieved, contributing to the development of an ocean-based economy and a better world.